2021
DOI: 10.22146/ijp.2729
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Severity Profile of COVID-19 Patient with Hypertension in Palu, Central Sulawesi

Abstract: Corona virus infection (COVID-19) is still an unsolved problem in Indonesia until this year. Apart from Java, other islands, including Sulawesi, were also badly affected. The very high mortality rate in Central Sulawesi (3.36%) poses a challenge for health workers; therefore, they should be well informed and with up-to-date information about correct therapeutic decisions. One of the most common comorbidities that often occurs with the severity and mortality of COVID-19 is hypertension. This study aims to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…NLR levels >9.47 were determined to be cut-offs that were substantially linked with in-hospital mortality in Ethiopian research, according to results of multivariate logistic regression analysis (adjusted odds ratio (AOR)=4.73, 95% CI: 1.19,33.68, P<0.02) (20). Renal function testing using urea has demonstrated a statistically significant correlation with patient outcome (P<0.001; r=0.435) (21). Meanwhile, serological analysis revealed a strong association between COVID-19 patient outcome and CRP, ferritin, and procalcitonin.…”
Section: Discussionmentioning
confidence: 99%
“…NLR levels >9.47 were determined to be cut-offs that were substantially linked with in-hospital mortality in Ethiopian research, according to results of multivariate logistic regression analysis (adjusted odds ratio (AOR)=4.73, 95% CI: 1.19,33.68, P<0.02) (20). Renal function testing using urea has demonstrated a statistically significant correlation with patient outcome (P<0.001; r=0.435) (21). Meanwhile, serological analysis revealed a strong association between COVID-19 patient outcome and CRP, ferritin, and procalcitonin.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the patient's blood pressure is not always accompanied by the severity of the disease. This might be due to the anti-hypertensive treatment that plays a role in the renin-angiotensin system (RAS) [ 23 ]. Some previous observational studies identified that RAS inhibition treatment might even reduce the risk of severe COVID-19 or mortality [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…We collected anthropometric and clinical data from 95 COVID-19 participants who were positive for SARS-CoV-2 (nose or throat swab real-time-polymerase chain reaction (rt-PCR) test) who received treatment in a hospital or underwent self-isolation under the monitoring of a health facility. The COVID-19 severity category is based on our preliminary research, which refers to the NIH guidelines [ 3 , 11 ]. We also selected 91 non-COVID-19 populations from outpatient clinics without matching age or sex for the baseline group.…”
Section: Methodsmentioning
confidence: 99%
“…To date, there have been 6.8 million cases of COVID-19 in Indonesia; 50.4% of them are women, and 48% have hypertension comorbidity, with a mortality rate of 2.4% [ 1 ], which is greater than the global mortality rate of 0.9% (May 2023) [ 2 ]. Most patients infected with SARS-CoV-2 were asymptomatic, but of the patients requiring hospitalization, 86% were classified as moderate and severe, with 17% of patients died [ 3 ].…”
Section: Introductionmentioning
confidence: 99%